Long and small noncoding RNAs during oocyte-to-embryo transition in mammals - Svoboda, Petr (Biochemical Society transactions, 2017)
Oocyte-to-embryo transition is a process during which an oocyte ovulates, is fertilized, and becomes a developing embryo. It involves the first major genome reprogramming event in life of an organism where gene expression, which gave rise to a differentiated oocyte, is remodeled in order to establish totipotency in blastomeres of an early embryo. This remodeling involves replacement of maternal RNAs with zygotic RNAs through maternal RNA degradation and zygotic genome activation. This review is focused on expression and function of long noncoding RNAs (lncRNAs) and small RNAs during oocyte-to-embryo transition in mammals. LncRNAs are an assorted rapidly evolving collection of RNAs, which have no apparent protein-coding capacity. Their biogenesis is similar to mRNAs including transcriptional control and post-transcriptional processing. Diverse molecular and biological roles were assigned to lncRNAs although most of them probably did not acquire a detectable biological role. Since some lncRNAs serve as precursors for small noncoding regulatory RNAs in RNA silencing pathways, both types of noncoding RNA are reviewed together.
Keywords: blastomery; Animals; RNAi; malá nekódující RNA; RNA dlouhá nekódující; oocyte; zygote; gastrulace; Humans; siRNA; Mammals; vývojová regulace genové exprese; LTR; lidé; zvířata; RNA, Small Untranslated; lncRNA; RNA, Long Noncoding; savci; Blastomeres; RNA Stability; stabilita RNA; Gastrulation; Gene Expression Regulation, Developmental